Formulation of Anisotropic Strength Criterion for Geotechnical Materials. (7th September 2020) - Chen, Liping; Wang, Sui; Chen, Bin; Niu, Xiaokai; Ying, Guogang; Wu, Bo
Abstract : A new nonlinear unified strength (NUS) criterion is obtained based on the spatially mobilized plane (SMP) criterion and Mises criterion. New criterion is a series of smooth curves between SMP curved triangle and Mises circle in the π plane and thereby unifies the strength criteria. The new criterion can reflect the effect of the intermediate principal stress and consider the strength nonlinearity of a material. Based on the fabric tensor, the anisotropic parameter A is defined, and the anisotropic equation is proposed and introduced into the NUS criterion to form a nonlinear unified anisotropic strength criterion. The new criterion can be used to predict the strength variation of granular materials and cohesive materials under three-dimensional stress and can present the strength anisotropy of the geomaterials. The validity of the new criterion was checked using rock and soil materials. It is shown that the prediction results for the criterion agree well with the test data.